Physical and physiological responses of soccer players performing repeated maximal efforts: thermo-neutral conditions vs simulated conditions of the FIFA World Cup Qatar 2022 - Chmura, P.; Liu, H.; Konefal, M.; Chmura, J.; Rokita, A.; Andrzejewski, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: This year, for the first time in history, the FIFA World Cup in Qatar 2022 will be moved to November and December in order to make the climatic conditions more bearable and less thermally troublesome for players (Konefal et al., 2021). According to the calculations of climatologists, despite the fact that during the tournament there will not be extremely high temperatures as in June and July, it can still reach close to, or even exceed 30 C degrees (Chodor et al., 2021). This study aimed to assess the capacity for repeated maximal effort (RME) of soccer players in the thermo-natural conditions (NC) and in simulated conditions for the 2022 FIFA World Cup in Qatar (QSC).